2016
DOI: 10.1093/mnrasl/slv202
|View full text |Cite
|
Sign up to set email alerts
|

The JCMT Gould Belt Survey: Understanding the influence of outflows on Gould Belt clouds

Abstract: Using JCMT Gould Belt Survey data from CO J = 3 → 2 isotopologues, we present a meta-analysis of the outflows and energetics of star-forming regions in several Gould Belt clouds. The majority of the regions are strongly gravitationally bound. There is evidence that molecular outflows transport large quantities of momentum and energy. Outflow energies are at least 20 per cent of the total turbulent kinetic energies in all of the regions studied and greater than the turbulent energy in half of the regions. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…All these findings imply that the outflow action has some impact on the local environment and cloud itself, but the contribution from outflow does not mainly drive turbulence. This observation is consistent with several other studies that suggest that turbulence is mostly driven by large-scale mechanisms (Ossenkopf & Mac Low 2002;Brunt et al 2009;Padoan et al 2009;Arce et al 2010;Mottram & Brunt 2012;Plunkett et al 2015;Drabek-Maunder et al 2016).…”
Section: Clumpsupporting
confidence: 93%
See 1 more Smart Citation
“…All these findings imply that the outflow action has some impact on the local environment and cloud itself, but the contribution from outflow does not mainly drive turbulence. This observation is consistent with several other studies that suggest that turbulence is mostly driven by large-scale mechanisms (Ossenkopf & Mac Low 2002;Brunt et al 2009;Padoan et al 2009;Arce et al 2010;Mottram & Brunt 2012;Plunkett et al 2015;Drabek-Maunder et al 2016).…”
Section: Clumpsupporting
confidence: 93%
“…They also reported that there is a better correlation between the outflow energy and turbulent energy, but the core turbulence is not driven by the local input from the outflows. However, Drabek-Maunder et al (2016) and Yang et al (2018) reported that there is not correlation between the turbulent and outflow energies. Urquhart et al (2018) found that the clump mass and evolutionary stage are uncorrelated.…”
Section: Clumpmentioning
confidence: 97%
“…On these scales, outflows may also contribute to the replenishment of turbulence within the star-forming region (see review by Mac Low & Klessen 2004, and references therein). However the importance of this contribution is being questioned and observations seem to produce contradictory results (Arce 2011;Drabek-Maunder et al 2016).…”
Section: Feedback Effects Of Protostellar Outflowsmentioning
confidence: 99%
“…Kim, Ostriker, & Kim (2014) and Kim & Ostriker (2015) also find that star formation properties, scale heights, and velocity dispersions in galaxies can be explained by supernova feedback. Still, internal cloud feedback from pre-main sequence winds is probably not generating the observed cloud line-widths, even though there is enough energy and momentum in the winds to do this; self-gravity seems to be involved instead (Drabek-Maunder et al 2016). Li & Burkert (2017) and Li (2017) also note that self-gravitational energy generation dominates turbulent energy decay in local molecular clouds.…”
Section: Introductionmentioning
confidence: 99%